Peran Ayah dalam Penanganan Perilaku Sibling Rivalry pada Anak Usia 4-5 Tahun Desa Baji Pa'mai Maros - Riskayanti, Riskayanti; Tahir, Yusuf; Hidayat, Muhammad Yusuf; Rahman, Ulfiani; Damayanti, Eka (NANAEKE: Indonesian Journal of Early Childhood Education, 2025)
This study aims to describe the causes of sibling rivalry, its impacts on child development, and the role of fathers in managing sibling rivalry behavior among children aged 4–5 years in Baji Pa’mai Village, Maros Regency. This research employed a qualitative approach using a phenomenological method. Data were collected through observation, interviews, and documentation involving five families with children aged 4–5 years, with fathers as the main informants. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the causes of sibling rivalry include parental attitudes, close age gaps, same gender, and birth order. The negative impacts of sibling rivalry are reflected in aggressive behaviors such as hitting, pushing, and verbal abuse, while the positive impacts encourage children’s independence, motivation, and sense of responsibility. The role of fathers in handling sibling rivalry is demonstrated through fair treatment toward children, spending quality time with them, mediating conflicts, and providing positive behavioral role models within the family. This study implies the importance of active father involvement in parenting to foster healthy interactions and support the social-emotional development of early childhood children.